Sexual dysfunction during the late postpartum period: prevalence and associated factors - Martínez-Galiano, Juan Miguel; Infante-Torres, Nuria; Ortiz-Esquinas, Inmaculada; Rubio-Álvarez, Ana; Ballesta-Castillejos, Ana; Hernandez-Martinez, Antonio (Frontiers in Psychiatry, 2026)
BackgroundAddressing women’s sexuality during the perinatal period receives little attention in research, and few studies are available. Furthermore, there is no consensus on the factors that influence the development of sexual dysfunction in the late postpartum period.ObjectiveDetermine the prevalence of sexual dysfunction in women during the late postpartum period and the factors associated with it.MethodA observational study was conducted with women who had given birth in Spain in 2024. Information was collected on sociodemographic variables, personal history, and sexual function. Mean differences (MD), adjusted mean differences (aMD), odds ratios (OR), and adjusted odds ratios (aOR) with their respective 95% confidence intervals (CI) were calculated, as appropriate. All analyses were performed using the statistical program SPSS 29.0.ResultsA total of 341 women participated. The prevalence of sexual dysfunction (FSFI scores <26.5) was 64.5%. The woman’s age (aOR: 1.10; 95%CI: 1.03-1.18), breastfeeding between 3 and 6 months postpartum (aOR: 3.34; 95%CI: 1.72-6.50), quality of life (SF-12) (aOR: 0.97; 95%CI: 0.95-0.99), and the WAST (aOR: 1.48; 95%CI: -1.13-1.93) are factors that influence the development of sexual dysfunction in the late postpartum period.ConclusionThe prevalence of sexual dysfunction in the medium term after childbirth is high. Younger age, non-breastfeeding status, good quality of life, and intimate partner relationships without violence are less likely to develop sexual dysfunction and have better sexual function.